A Dynamic Theory of Regulatory Capture - Alessandro De Chiara; Marco Schwarz (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2020)
Firms have incentives to influence regulators' decisions. In a dynamic setting, we show that a firm may prefer to capture regulators through the promise of a lucrative future job opportunity (i.e., the revolving-door channel) than through a hidden payment (i.e., a bribe). This is because the revolving door publicly signals the firm's eagerness and commitment to reward friendly regulators, which facilitates collusive equilibria. Moreover, the revolving-door channel need not require an explicit agreement between the firm and the regulator, but may work implicitly giving rise to an industry norm. This renders ineffective standard anti-corruption practices, such as whistle-blowing protection policies. We highlight that closing the revolving door may give rise to other inefficiencies. Moreover, we show that cooling-off periods may make all players worse off if timed wrongly. Opening the revolving door conditional on the regulator's report may increase social welfare.
Keywords: D82; J45; K23; L14; L51; 330; collusion; corruption; dynamic games; experts; regulation; regulatory capture; revolving door